Social Media for English Language Enhancement and Digital Literacy Skills: A Pathway to Global Citizenship - Fini Widya Fransiska (Education Studies and Teaching Journal (EDUTECH), 2024)
The use of social media as a tool to improve English language skills and digital literacy among students has been the subject of significant research. This research aims to explore the contribution of social media in the development of English speaking skills and digital literacy in various global contexts. The research method uses a systematic approach by conducting a literature review of relevant articles from international databases. The research results show that social media provides great potential in facilitating collaborative learning, increasing learning motivation, and developing online content evaluation skills among students. The implication of this research is the importance of integrating social media in educational practices to strengthen students' English language and digital literacy skills, as well as prepare them for future global challenges.